-3/2m+2/3m=-1/2(1/2m-3/2)-8/3(1/2m+1)

Simple and best practice solution for -3/2m+2/3m=-1/2(1/2m-3/2)-8/3(1/2m+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3/2m+2/3m=-1/2(1/2m-3/2)-8/3(1/2m+1) equation:


m in (-oo:+oo)

(-3/2)*m+(2/3)*m = (-1/2)*((1/2)*m-(3/2))-((8/3)*((1/2)*m+1)) // - (-1/2)*((1/2)*m-(3/2))-((8/3)*((1/2)*m+1))

(8/3)*((1/2)*m+1)-((-1/2)*((1/2)*m-(3/2)))+(-3/2)*m+(2/3)*m = 0

(1/2)*((1/2)*m-3/2)+(8/3)*((1/2)*m+1)+(-3/2)*m+(2/3)*m = 0

1/2*(1/2*m-3/2)+8/3*(1/2*m+1)+(-3*m)/2+(2*m)/3 = 0

(1/2*2*3*(1/2*m-3/2))/(2*3)+(2*8/3*3*(1/2*m+1))/(2*3)+(-3*3*m)/(2*3)+(2*2*m)/(2*3) = 0

1/2*2*3*(1/2*m-3/2)+2*8/3*3*(1/2*m+1)-3*3*m+2*2*m = 0

19/2*m-9*m+4*m+23/2 = 0

1/2*m+4*m+23/2 = 0

9/2*m+23/2 = 0

(9/2*m+23/2)/(2*3) = 0

(9/2*m+23/2)/(2*3) = 0 // * 2*3

9/2*m+23/2 = 0

9/2*m+23/2 = 0 // - 23/2

9/2*m = -23/2 // : 9/2

m = -23/2/9/2

m = -23/9

m = -23/9

See similar equations:

| x-(12)=-4 | | 2x+(2/(2x-12)) | | -7(4t+14)=-20-15t | | -7x=-28+11-4 | | y-19.25=x^2+6x+30.25 | | 3-x=2(1-4x)-6 | | 7t-12-2t=9+5t | | 2x+(2/2x-12) | | 2.5x+.5x=6+3.5 | | -(-20-4s)=-2(s+8) | | -8r=4(r-3) | | -50=19+y | | -5n-10=-(8n-1)-8n | | y=(x-2)-1 | | -(30)-(10)-43= | | 25200*(1/9) | | 80=1.8C+32 | | -255=-15k | | 10h=2(4h+13) | | 3a+9-6=21 | | 9.95m=m | | -3(x+5)=-3x-15 | | -18+2(j-12)=-12j | | 25200*(1/10) | | 4.95m+49.95=m | | -0.75x-2=0.25x | | y-6=-5/4(x+1) | | 6y=-3x(2)-4 | | (x+2)*3=(x-10)*7 | | 6(7g-16)=4(6g+12) | | 52=p | | -8(-6x+6)=-4x+4 |

Equations solver categories